2022
DOI: 10.1139/cjpp-2022-0058
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of chloride channel-3 enhances cisplatin sensitivity of cholangiocarcinoma cells though inhibiting autophagy

Abstract: Chemotherapy is one of the most important strategies in the treatment of cancer, however, chemo-resistance restricts the effect of chemotherapy. Growing reports suggest that chloride channel-3 (ClC-3) is involved in regulating the sensitivity of multiple chemotherapeutic agents in the chemotherapy of various tumors, while its role in the chemotherapy of cholangiocarcinoma (CCA) is still poorly understood. Herein, we observed that ClC-3 was highly expressed in CCA chemo-resistant tissues and CCA cisplatin-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Accumulating studies have suggested that ClC-3 is expressed in a number of cancer cells and serves a well-defined role in cell proliferation, apoptosis and metastasis (12)(13)(14)(15). Furthermore, abnormality of ClC-3 expression has been demonstrated to be associated with the development of drug resistance, including PTX, cisplatin and etoposide resistance, in various tumor cells (16)(17)(18)(19). However, the potential regulatory mechanism of ClC-3 in PTX resistance of NSCLC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have suggested that ClC-3 is expressed in a number of cancer cells and serves a well-defined role in cell proliferation, apoptosis and metastasis (12)(13)(14)(15). Furthermore, abnormality of ClC-3 expression has been demonstrated to be associated with the development of drug resistance, including PTX, cisplatin and etoposide resistance, in various tumor cells (16)(17)(18)(19). However, the potential regulatory mechanism of ClC-3 in PTX resistance of NSCLC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Common ion channels include cation channels (potassium-, calcium-, and sodium-ion channels) as well as the most important anion channel, for chloride ions. 10,11 Among them, the chloride channel (TMEM16A) is involved in many malignancies, where it is not only overexpressed but may also induce drug resistance. 12 To the best of our knowledge, blocking chloride channels to inhibit chemoresistance for enhancing the efficacy of chemotherapy has not yet been reported.…”
mentioning
confidence: 99%